What's In A Name? Malay Seals As Onomastic Sources: (Apa Ada pada Nama? Cap Mohor Melayu sebagai Sumber Onomastik) (Malay Literature, 2018)
Most studies of Malay names to date have been based on ethnographic and literary sources. This article presents a new dataset for Malay onomastics, namely Islamic seals from Southeast Asia, inscribed in Arabic script and dating from the late 16th to early 20th century, over half of which bear a personal name. A high proportion of these seals are of sovereigns, and Malay seals are thus an exceptionally valuable primary source for regnal names. Yet while in Malay texts and chronicles the use of personal names is generally avoided in favour of kinship terms, relational names, titles and descriptive epithets, Malay seals are almost invariably inscribed with standard Arabic-Islamic personal names. This feature should be interpreted in the context of the image of self which the sealholder wished to project to the outside world, in which his or her Islamic identity, and membership of the universal ummah, was of prime importance.Keywords: Malay names, onomastic, Malay seals, regnal names, Islamic names